2009
DOI: 10.2143/ac.64.3.2038016
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acid supplements improve the cardiovascular risk profile of subjects with metabolic syndrome, including markers of inflammation and auto-immunity

Abstract: A (2009) Omega-3 fatty acid supplements improve the cardiovascular risk profile of subjects with metabolic syndrome, including markers of inflammation and auto-immunity. Acta Cardiologica, 64

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 35 publications
(27 reference statements)
2
62
1
4
Order By: Relevance
“…This was confirmed also by our group, n-3 PUFA intake gave a better lipid profile and a better improvement of coagulation, fibrinolytic, inflammatory parameters, and blood pressure than placebo [12,13]. The same conclusions were reached by Ebrahimi et al [29]: n-3 PUFA improve the cardiovascular risk profile of subjects with metabolic syndrome (MS), having effects on weight, systolic blood pressure, lipid profile, and markers of inflammation and autoimmunity. On the other side Simão et al [30] reported that, even if an intake of n-3 PUFA gave a decrease of Tg and an increase of the total antioxidant capacity (TRAP) in patients with MS, there was an increase of LDL-C levels and insulin resistance after n-3 PUFA intake.…”
Section: Discussionsupporting
confidence: 82%
“…This was confirmed also by our group, n-3 PUFA intake gave a better lipid profile and a better improvement of coagulation, fibrinolytic, inflammatory parameters, and blood pressure than placebo [12,13]. The same conclusions were reached by Ebrahimi et al [29]: n-3 PUFA improve the cardiovascular risk profile of subjects with metabolic syndrome (MS), having effects on weight, systolic blood pressure, lipid profile, and markers of inflammation and autoimmunity. On the other side Simão et al [30] reported that, even if an intake of n-3 PUFA gave a decrease of Tg and an increase of the total antioxidant capacity (TRAP) in patients with MS, there was an increase of LDL-C levels and insulin resistance after n-3 PUFA intake.…”
Section: Discussionsupporting
confidence: 82%
“…Lastly, LC ω-3 PUFAs modulate T-cell signaling and proliferation (22). In addition to a wealth of cell and animal experimental studies, LC ω-3 PUFAs have been shown to hold antiinflammatory properties in epidemiologic studies (11,12) and randomized clinical trials (13)(14)(15). They are further hypothesized to have chemoprotective properties for endometrial cancer (and other estrogendependent cancers), as inhibition of inflammation via NF-κB and COX-2 is associated with reduced estrogen synthesis (24)(25)(26), which is thought to be a critical component for endometrial proliferation (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Those taking the supplements were found to have lower markers of autoimmunity and inflammation, as well as more weight loss, compared to people who did not take the supplements [16].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 92%